Application of trio-based whole-exome sequencing in fetal ultrasound anomalies: a single-center retrospective study of 454 cases - Yu, Dongyi; Feng, Dairong; Qu, Jiangbo; Nie, Lei; Liu, Qian; Gao, Lu; An, Wenzhen; Liu, Na; Fang, Yuying (Frontiers in Genetics, 2025)
This study assessed the diagnostic effectiveness of trio-WES compared to CMA in fetuses with ultrasound anomalies and explored optimal prenatal testing strategies. A retrospective review included 454 fetuses who underwent trio-WES and/or CMA between 2020 and 2023. Cases were divided into four groups and 19 subgroups based on improvements in diagnosing ultrasound anomalies, demonstrating that trio-WES offers greater diagnostic value than CMA—especially for skeletal and multisystem defects, as well as ultrasound findings used to determine diagnostic yields. Trio-WES achieved a diagnostic yield of 22.7% (103/454), exceeding CMA by 17%. The highest diagnostic rates were observed in skeletal anomalies (39.2%) and multisystem anomalies (29.1%). Subgroup analysis showed higher yields in crystalline lens anomalies (60.0%) and cardiac rhabdomyoma (57.1%). Trio-WES significantly enhances prenatal diagnosis of ultrasound anomalies and provides additional diagnostic insights over CMA, particularly for skeletal, multisystem defects, and specific structural subgroups. Importantly, trio-WES helps clarify the mechanisms of ROH and assess its pathogenicity, aiding in detecting imprinted disorders. These findings support including trio-WES in prenatal testing protocols for congenital malformations and establish a framework for its clinical application.